DETERMINANTS GROWTH OF TOTAL ASSETS BY BANK SPECIFIC VARIABLE AND MARKET SHARE IN ISLAMIC BANKING IN INDONESIA, PERIOD 2011 - 2015 - SETYAWATI, IRMA; SUROSO, SUGENG (Universitas Negeri Semarang, 2016)
This research was conducted at Islamic banking in Indonesia, from January 2011 to December 2015 with a month-use data. This study used the design verification to see bank-specific variables and market share effects on the growth of the total assets of Islamic banking in Indonesia. The results showed that the variables of specific banks and the market share represented by finance deposit ratio, capital adequacy ratio, the ratio of operating expenses to total assets, the ratio of income of non-financing with total assets, non-performing financing and market share jointly significant effect on growth the value of assets of Islamic banking in Indonesia.